Evolution of histone 2A for chromatin compaction in eukaryotes - Macadangdang, Benjamin R (eLife Sciences Publications, Ltd, 2014)
During eukaryotic evolution, genome size has increased disproportionately to nuclear volume, necessitating greater degrees of chromatin compaction in higher eukaryotes, which have evolved several mechanisms for genome compaction. However, it is unknown whether histones themselves have evolved to regulate chromatin compaction. Analysis of histone sequences from 160 eukaryotes revealed that the H2A N-terminus has systematically acquired arginines as genomes expanded. Insertion of arginines into their evolutionarily conserved position in H2A of a small-genome organism increased linear compaction by as much as 40%, while their absence markedly diminished compaction in cells with large genomes. This effect was recapitulated in vitro with nucleosomal arrays using unmodified histones, indicating that the H2A N-terminus directly modulates the chromatin fiber likely through intra- and inter-nucleosomal arginine–DNA contacts to enable tighter nucleosomal packing. Our findings reveal a novel evolutionary mechanism for regulation of chromatin compaction and may explain the frequent mutations of the H2A N-terminus in cancer. DOI: http://dx.doi.org/10.7554/eLife.02792.001